Microsatellite Instability in Chicken Lymphoma Induced by Gallid Herpesvirus 2 - Yao, Da-Wei (Public Library of Science, 2013)
Microsatellite instability (MSI) has been found in a range of human tumors, and little is known of the links between MSI and herpesvirus. In order to investigate the relationship between MSI and Gallid herpesvirus 2 (GaHV-2)-induced lymphoma, fifteen Marek’s disease (MD) lymphomas were analyzed through using 46 microsatellite markers, which were amplified by PCR from DNA specimens of lymphoma and normal muscular tissues from the same chicken. PCR products were evaluated by denaturing polyacrylamide gel electrophoresis for MSI analysis. MSI was proved in all lymphomas, at least in one locus. Thirty of the 46 microsatellite markers had microsatellite alterations. These results suggested that GaHV-2-induced lymphoma in chickens is related to MSI, and this is the first report to demonstrate that MSI is associated with the GaHV-2 induced lymphoma in chicken.